An Extremely Rare Presentation of Four Coronary Anomaly Patterns Originating from the Right Coronary Sinus - Nabil Braiteh; Wajeeh Rehman; Wajiha Ali; Owais Ahmed (Case Reports in Cardiology)
Background. “Coronary anomaly” is defined as the coronary feature or pattern seen in <1% of the population. The most common CAAs are anomalies of origin, specifically having a separate LCX and LAD origin with an incidence of 0.41%. The second most common anomaly is the LCX arising from the RCA (0.37%). Treatment options include CABG, coronary unroofing, reimplantation, or medical therapy. Case Presentation. We present the case of an 85-year-old male who presents with an acute coronary syndrome who was found to have an extremely rare combination of different coronary anomaly patterns including left main coronary artery (LMCA) atresia, small LAD arising posteriorly from the right coronary cusp, anomalous left circumflex artery arising from the RCA, and an anomalous LAD arising from the left circumflex artery which is originating from the RCA. Conclusions. To the best of our knowledge, this is the first case report to describe four coronary anomalies in a single patient. When CAAs are diagnosed, it is of utmost importance for cardiologists to do further imaging and workup that might include a stress test to be able to offer patients the best management options.